The Effectiveness of Psychosocial Interventions for Elder Abuse in Community Settings: A Systematic Review and Meta-Analysis - Shen, Yan; Sun, Fei; Zhang, Anao; Wang, Kaipeng (Frontiers in Psychology, 2021)
Background: As a global public health concern, elder abuse negatively affects health, psychosocial wellbeing and mortality among elders. Research and practice efforts made to explore effective prevention and intervention strategies are growing. Despite the growing number of intervention studies on elder abuse, research synthesis on the empirical literature seems lacking. Objectives: This study aims to identity the pooled effect size of prevention and interventions targeted ultimate and intermediate outcomes for elder abuse occurred in community settings. Design: Following the Cochrane guideline, our team searched across eight electronic databases and manually searched reference lists of eligible studies and existing systematic reviews for all potential eligible studies. Results: A random-effects model of 51 effect size estimates reported an overall positive and statistically significant treatment effect of psychosocial interventions for elder abuse, d = 0.63, p < 0.05. The overall treatment effect was approaching statistical significance at .10 level for ultimate outcomes, d = .32, p = .09, and intermediate outcomes, d=.75, p = .10. An overall significant effect size was found among family-based interventions, d = .59, p < .05), and interventions targeting older adults and their caregivers, d = 0.45, p < 0.05. Conclusion: Existing evidence supports an overall significant effect for psychosocial interventions for elder abuse. Interventions that used family-based model, combined education and supportive services, and targeted both caregivers and elders, showed significant effect size, suggesting such features being considered in elder abuse intervention design. Future intervention research is needed to shed light on the link between intervention activities and ultimate change in elder abuse behaviors.